Comparison of Human Interpretation and a Rule-Based Algorithm for Instrumented Sit-to-Stand Test - Jung, Hee-Won (Ann Geriatr Med Res, 2021)
BACKGROUND: The five times sit-to-stand test (5STS) is one of the most commonly used tests to assess the physical performance of lower extremities. This study assessed the correlation between human interpretation (5STS(human)) and a rule-based algorithm (5STS(rule)) using instrumented 5STS with two sensors. METHODS: We analyzed clinical records of 148 patients who visited the geriatric outpatient clinic of Asan Medical Center between December 2020 and March 2021 and underwent physical performance assessment using the electronic Short Physical Performance Battery (eSPPB) protocol. For STS, time-weight and time-distance curves were constructed using a loadcell and light detection and ranging (LiDAR). We manually assessed the grids of these curves to calculate 5STS(human), while 5STS(rule) used an empirical rule-based algorithm. RESULTS: In the study population, the mean 5STS(human) and 5STS(rule) times, i.e., 12.2±0.4 and 11.4±0.4 seconds, respectively, did not differ significantly (p=0.232). Linear regression analysis showed that 5STS(human) and 5STS(rule) were positively correlated (β=0.99, R(2)=0.99). The measures also did not differ (p=0.381) in classifying sarcopenia according to the Asian Working Group Society criteria, with C-indices of 0.826 for 5STS(human) and 0.820 for 5STS(rule). CONCLUSION: An empirical rule-based algorithm correlated with human-interpreted 5STS and had comparable classification ability for sarcopenia.